A case study of critique: Critical perspectives on critical accounting. (March 2017) - Dillard, Jesse; Vinnari, Eija
Abstract: As accounting academics, we have a responsibility to act in the public interest as conscience, critic and counselor of society regarding economic, social and environmental justice. In fulfilling this responsibility, we are concerned with how accounting, accountants, and accountability regimes can facilitate democracy by serving the needs of pluralistic communities, giving particular attention to the various underserved constituencies. Informed by Flyvbjerg's (2001) notion of phronetic social science research that matters, we reviewed 353 articles published in Critical Perspectives on Accounting from 1990 to 2014 identifying the focal constituency(s), the injustice(s) addressed, the groups or institutions responsible for the injustice as well as the proposals for social and political praxis outlined in the studies. Our review indicates that generally the studies identify a somewhat focused, though salient and appropriate, set of economic, social and/or environmental injustices experienced by various constituencies, and to some extent, the studies consider the context and conditions that perpetuate the inequality and injustices. However, as the field matures, there is a need for more robust development of the social and political implications of critical accounting research and for articulating the ideas and implications as action programs. Further, our review suggests that several relevant constituencies such as non-human animals, children, future generations, developing nations, and gender and sex/uality minorities have received little or no attention in the current literature.